A CASE STUDY ON EVALUATING PERSONNEL AND JOBS JOINTLY WITH FUZZY DISTANCE - Ozdaban, Ismail; OZKAN, Coskun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
In this research, a case study of fuzzy approach on personnel evaluation and job evaluation together was performed. A newer fuzzy distance measurement formula was developed and used to determine fuzzy distances. Although there have been many researches on personel evaluation and job evaluation concepts together, it is not found any research in which these to concepts were examined. Evaluating personel and job together gave some advantages like compability of data, useness of model and managing the two concepts together. Model gave detailed information on an organization. Results showed that suggested formula and method could be used for small, medium or large companies easily, and allowed to evaluate two concepts together even there are many personel and jobs in an organization.